2022
DOI: 10.1155/2022/3710449
|View full text |Cite
|
Sign up to set email alerts
|

IP-Se-06, a Selenylated Imidazo[1,2-a]pyridine, Modulates Intracellular Redox State and Causes Akt/mTOR/HIF-1α and MAPK Signaling Inhibition, Promoting Antiproliferative Effect and Apoptosis in Glioblastoma Cells

Abstract: Glioblastoma multiforme (GBM) is a notably lethal brain tumor associated with high proliferation rate and therapeutic resistance, while currently effective treatment options are still lacking. Imidazo[1,2-a]pyridine derivatives and organoselenium compounds are largely used in medicinal chemistry and drug development. This study is aimed at further investigating the antitumor mechanism of IP-Se-06 (3-((2-methoxyphenyl)selanyl)-7-methyl-2-phenylimidazol[1,2-a]pyridine), a selenylated imidazo[1,2-a]pyridine deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…The results obtained corroborated those of Santos and collaborators who, through the analysis of a compound derived from selenylated imidazopyridine, obtained a significant reduction in cell counts when compared to cells not treated with the compound; that is, they reported that imidazopyridine derivatives have an antiproliferative potency in the cells of glioblastoma [ 30 ]. Another study by Almeida and collaborators using the same imidazopyridine-derived compound demonstrated an inhibition of cell growth in 90% of breast cancer cell lines when compared to untreated controls [ 13 ].…”
Section: Resultssupporting
confidence: 87%
“…The results obtained corroborated those of Santos and collaborators who, through the analysis of a compound derived from selenylated imidazopyridine, obtained a significant reduction in cell counts when compared to cells not treated with the compound; that is, they reported that imidazopyridine derivatives have an antiproliferative potency in the cells of glioblastoma [ 30 ]. Another study by Almeida and collaborators using the same imidazopyridine-derived compound demonstrated an inhibition of cell growth in 90% of breast cancer cell lines when compared to untreated controls [ 13 ].…”
Section: Resultssupporting
confidence: 87%
“…The GSH redox system plays an important role in cell survival and apoptosis [ 52 , 53 , 54 ], and inhibition of HPGDS was found to result in a downregulation of the GSH levels and a reduction in cellular drug resistance. Considering that the JNK pathway plays an important role in promoting apoptosis in glioma, and a variety of GSTs can regulate the activation of the JNK signaling pathway [ 42 , 55 , 56 ], we speculate that the resistance-promoting function of HPGDS is partly attributable to the inhibition of apoptosis resulting from downregulated activation of the JNK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These methodologies generally require high-cost equipment, result in low yield, and use toxic solvents, which reduces the sustainability of the process. In line with our interest in discovering and developing a new sustainable, efficient methodologies for biologically active compounds and patient-compliant alternative for leishmaniasis treatment [10][11][12][13][14][15][16][17], our research group aimed to yield natural-based bioactive compounds with multitarget properties. To achieve this purpose, we designed a scalable, easy-to-replicate, and inexpensive synthetic route to obtain flavonol and chalcone analogs.…”
Section: Of 23mentioning
confidence: 99%